Analysis of Elementary School Students’ Leisure Time during the Covid-19 Pandemic - Mugianti, Dinnida Sulistiani; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (Indonesian Journal of Multidiciplinary Research, 2022)
Unforeseen circumstances in the form of the COVID- 19 disease outbreak have brought urgent changes to various sectors. The government's recommendation to stay at home and physical and social distancing must be followed by a change in the face-to-face learning mode to online so that a lot of free time is left at home. The purpose of this study was to analyse the planning of activities carried out in free time for elementary school students’ during the covid-19 pandemic. The study used a quantitative approach using a pre-experimental method in the form of a one-group pre-test - post-test design. The results of the research show that the average post-test score of students’ is 84.7%, greater than the average pre-test score of 69.3% which has a difference of 15.4%. Therefore, it is hoped that students’ can plan positive activities to fill their spare time during the COVID-19 pandemic.